Integrin α5 mediates cancer cell-fibroblast adhesion and peritoneal dissemination of diffuse-type gastric carcinoma. (1st February 2022) - Miyamoto, Shingo; Nagano, Yoshiko; Miyazaki, Makoto; Nagamura, Yuko; Sasaki, Kazuki; Kawamura, Takeshi; Yanagihara, Kazuyoshi; Imai, Toshio; Ohki, Rieko; Yashiro, Masakazu; Tanaka, Masato; Sakai, Ryuichi; et al.
Abstract: Diffuse-type gastric carcinoma (DGC) has a poor prognosis due to its rapid diffusive infiltration and frequent peritoneal dissemination. DGC is associated with massive fibrosis caused by aberrant proliferation of cancer-associated fibroblasts (CAFs). Previously, we reported that direct heterocellular interaction between cancer cells and CAFs is important for the peritoneal dissemination of DGC. In this study, we aimed to identify and target the molecules that mediate such heterocellular interactions. Monoclonal antibodies (mAbs) against intact DGC cells were generated and subjected to high-throughput screening to obtain several mAbs that inhibit the adhesion of DGC cells to CAFs. Immunoprecipitation and mass spectrometry revealed that all mAbs recognized integrin α5 complexed with integrin β1. Blocking integrin α5 in DGC cells or fibronectin, a ligand of integrin α5β1, deposited on CAFs abrogated the heterocellular interaction. Administration of mAbs or knockout of integrin α5 in DGC cells suppressed their invasion led by CAFs in vitro and peritoneal dissemination in a mouse xenograft model. Altogether, these findings demonstrate that integrin α5 mediates the heterotypic cancer cell-fibroblast interaction during peritoneal dissemination of DGC and may thus be a therapeutic target. Highlights: Monoclonal antibodies blocking cancer cell-fibroblast adhesion were generated. All monoclonal antibodies recognized integrin α5 expressed on gastric cancer cells. Blocking integrin α5-fibronectin interaction inhibited the heterocellular adhesion. Targeting integrin α5 suppressed invasion and metastasis of gastric cancer cells.